Biogeographic deconstruction of phylogenetic and functional diversity provides insights into the formation of regional assemblages. Issue 5 (5th April 2022) - Molina‐Venegas, Rafael; Ottaviani, Gianluigi; Campetella, Giandiego; Canullo, Roberto; Chelli, Stefano
Abstract : Evolutionary history and environmental filtering shape the phylogenetic and functional structure of regional assemblages. However, detecting the footprint of such eco‐evolutionary drivers is challenging because these may often counter each other's signature. Here, we examined whether a biogeographic deconstruction approach of phylogenetic (PD) and functional diversity (FD) patterns may help in identifying eco‐evolutionary signals in extant regional assemblages. As model system, we used forest understorey angiosperms found in three regions of Italy (Alpine, Mediterranean, Continental). We quantified PD and FD of all species inhabiting the three regions (regional assemblages). Then, we computed PD and FD for the subsets of species restricted to each region (biogeographic elements), also examining diversity patterns of species found across the three regions (widespread element). We used aboveground and belowground traits capturing major plant functions to calculate FD. Additionally, we assessed FD patterns decoupled from phylogeny. We found that species restricted to climatically harsh regions (Alpine and Mediterranean elements) were phylogenetically and functionally clustered, whereas widespread species were characterised by overdispersion. Species confined to the climatically intermediate (Continental) region were randomly sorted. By including all species occurring within a region, the patterns found for the region‐restricted species blurred. Phylogenetically decoupled FD patterns were qualitatively similar to non‐decoupled ones with the exception of the Alpine element, where we detected a clear signature of functional differentiation between closely related species. This suggests that recent speciation events contributed to shaping the Alpine flora. Compared to the belowground compartment, aboveground traits showed a more coherent pattern with that of all‐trait FD – likely because most biomass is allocated aboveground in forest understoreys. This biogeographic deconstruction study illustrates which type of eco‐evolutionary insights can be gained by implementing multifaceted and integrated approaches at the macroecological scale.